Weed-soybean interference studies in Brazil - Pitelli, R. A. (Springer Nature, 1992)
Recently, a notable shift in weed patterns has occurred in some soybean growing regions, as a result of tillage system change and herbicide use. The weed communities are very diversified and strongly interfere with soybean growth and productivity, especially when the shading of superior leaves of the canopy occurs. Some changes to certain agricultural practices, such as cultivars, row spacing and sowing density, were studied and were considered suitable for the establishment of an integrated weed management system under Brazilian conditions. -from Author
Keywords: integrated weed management; soybean; weed control; Brazil